Perspectives of physical activity in combating metabolic syndrome: insights from a multi-ethnic urban population - Ali, Bushra; Evans, Tim; Cohen, Rhonda; Elliott, Anne (Frontiers in Public Health, 2025)
The United Arab Emirates is experiencing a rising burden of non-communicable diseases, particularly metabolic syndrome (MetS), driven by rapid urbanization and lifestyle changes. In Dubai's diverse population, where expatriates constitute 85% of residents, understanding perspectives on physical activity (PA) is essential for effective prevention strategies. This qualitative study explored stakeholder experiences and views on PA as a preventive measure for MetS. Semi-structured interviews were conducted with 20 stakeholders, including policy officials, gym owners, trainers, gym members, and inactive individuals, recruited through purposive and snowball sampling. Data were analyzed using thematic analysis and Hofstede's cultural framework to examine cultural influences on PA behaviors. Results indicated broad recognition of PA's importance in managing MetS but identified significant cultural and environmental barriers to participation. Key themes included cultural perceptions shaping engagement with PA and infrastructure challenges. These findings highlight the need for culturally tailored interventions and multisectoral collaboration to promote active lifestyles in Dubai's multi-ethnic context. This research offers valuable insights to guide public health initiatives aiming to reduce the burden of MetS through culturally sensitive approaches suited to this unique urban environment.